2023
DOI: 10.1002/jgf2.617
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic excellence in primary care

Abstract: Diagnostic excellence is based on six fundamental principles of healthcare quality proposed by the Institute of Medicine in 2001, which state that diagnoses must be safe, effective, patient‐centered, timely, efficient, and equitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Being proficient in the operation of the system prevents the deterioration of patient’s quality of life and assists them in living better [ 8 , 9 ]. All these ultimately contribute to the quality of diagnosis and will likely be encompassed by the slogan of diagnostic excellence [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being proficient in the operation of the system prevents the deterioration of patient’s quality of life and assists them in living better [ 8 , 9 ]. All these ultimately contribute to the quality of diagnosis and will likely be encompassed by the slogan of diagnostic excellence [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variables cannot be selected chaotically and in too many a number, but in an orderly manner, with due respect for the safety and comfort of the patient, for time and resource constraints, optimally with each subsequent variable adding evidence, revealing and confirming causality, thus increasing confidence in the diagnosis. Implementation of this recommendation is regarded as diagnostic excellence [5][6][7][8][9][10].…”
Section: Health and Normalitymentioning
confidence: 99%
“…CDSSs are computer-based tools that assist medical professionals in a wide range of clinical decisions, including diagnosis, treatment planning, medication ordering, preventive care, and patient education [ 3 ]. Research has shown that CDSS interventions significantly improve diagnostic accuracy [ 4 ], a key aspect of diagnostic excellence [ 5 ]. For instance, interventions involving a CDSS in the diagnosis of common chronic diseases demonstrated significant improvements [ 6 ].…”
Section: Introductionmentioning
confidence: 99%